The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.14336/ad.2017.1031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rhythmic Auditory Cueing on Aging Gait: A Systematic Review and Meta-Analysis

Abstract: Rhythmic auditory cueing has been widely used in gait rehabilitation over the past decade. The entrainment effect has been suggested to introduce neurophysiological changes, alleviate auditory-motor coupling and reduce cognitive-motor interferences. However, a consensus as to its influence over aging gait is still warranted. A systematic review and meta-analysis was carried out to analyze the effects of rhythmic auditory cueing on spatiotemporal gait parameters among healthy young and elderly participants. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 173 publications
2
56
0
4
Order By: Relevance
“…Studies have shown that rhythmic auditory cueing might also be an efficient tool to counteract dual-task-associated information-processing constraints. 121 , 122 For instance, Lohnes and Earhart 104 suggested that rhythmic entrainment might allow alleviation in gait performance by possibly freeing up cognitive resources for dual-task execution. Although dual-task performance has been shown to reduce performance in people with cerebral palsy, 26 we did not identify any study analyzing the effects of rhythmic auditory cueing under higher information-processing constraints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that rhythmic auditory cueing might also be an efficient tool to counteract dual-task-associated information-processing constraints. 121 , 122 For instance, Lohnes and Earhart 104 suggested that rhythmic entrainment might allow alleviation in gait performance by possibly freeing up cognitive resources for dual-task execution. Although dual-task performance has been shown to reduce performance in people with cerebral palsy, 26 we did not identify any study analyzing the effects of rhythmic auditory cueing under higher information-processing constraints.…”
Section: Discussionmentioning
confidence: 99%
“… 49 Moreover, as a cheap 50 and viable 51 treatment strategy, this approach can provide substantial benefits in developing countries, where prevalence of cerebral palsy due to socioeconomic factors is more prominent. 52 , 53 We identified high-quality systematic reviews analyzing the effects of external auditory cueing on gait performance among healthy, 121 Parkinsonism 54 56 , 122 and stroke participants. 57 59 However, to the best of our knowledge, no systematic or narrative analysis has been carried out to analyze the effects of auditory entrainment on gait in people with cerebral palsy.…”
Section: Introductionmentioning
confidence: 99%
“…Thaut et al succeeded in the rhythmic facilitation of gait for Parkinson's disease [35] and stroke patients [36], and also in the rhythmic cuing of reaching movements for stroke patients [37]. Ghai et al reviewed further benefits of auditory cuing for gait impairments caused by aging [38], cerebral palsy [39], and Parkinson's disease [40]. Thaut provided an overview about therapeutic usable effects of music in neuromotor rehabilitation [41].…”
Section: Introductionmentioning
confidence: 99%
“…Several of the systematic reviews and meta-analyses have also suggested a similar temporal course for auditory-motor training regimens to allow enhancements in motor performance. [29][30][31][32][33][34] In the present research, we aim to address the limitations of the experimental design used, and also to elucidate the influence of auditory feedback on motor learning. An expanded intermodal auditoryproprioceptive training protocol has been developed to investigate the efficacy of real-time auditory information on proprioceptive motor learning.…”
Section: Introductionmentioning
confidence: 99%